If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(31.25 + -0.5) + 4y = 250 Combine like terms: 31.25 + -0.5 = 30.75 8(30.75) + 4y = 250 Multiply 8 * 30.75 246 + 4y = 250 Solving 246 + 4y = 250 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-246' to each side of the equation. 246 + -246 + 4y = 250 + -246 Combine like terms: 246 + -246 = 0 0 + 4y = 250 + -246 4y = 250 + -246 Combine like terms: 250 + -246 = 4 4y = 4 Divide each side by '4'. y = 1 Simplifying y = 1
| x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) |